Guía gastronómica de platos típicos de la parroquia Guaytacama del cantón Latacunga provincia Cotopaxi. - Gaspata Quisaguano, Silvia Maribel (2018)
The present research project is based on the study of the typical gastronomy of Guaytacama Parish, with the purpose of gathering the necessary information that strengthens the development in the cultural, economic and touristic place of study through the elaboration of a gastronomic guide. Through the guide is intended to disseminate, and promote culinary traditions and customs and publicize the variety of typical dishes that exist, to perform the researching process was raised three specific objectives, which allowed the collection of primary and secondary information, through the first objective was the situational diagnosis of the area through the analysis of the geographic - environmental, historical - cultural, socio - economic factor, in the second objective the respective inventory was made, for the record of the typical gastronomy the methodology of the National Institute was used of Cultural Heritage (INPC), where it was possible to register a total of 14 typical dishes of the parish and their respective neighborhoods that were supported by photographic record in field trips and views of markets, restaurants, typical food fairs, resulting in of the typical dishes mostly a low sensibility which means that it maintains the current gastronomy in the parish. To conclude, the information collected through the inventory was systematized and a guide was designed which will serve as a gastronomic information tool for the Guaytacama parish, which in turn generates benefits for the inhabitants and tourists, both national and foreign. Through this study, a positive socio-economic impact is generated, which helps to safeguard the knowledge and traditions of the culinary culture. When carrying out this project, it can be said that it has contributed directly to the inhabitants, capturing the information of recipes of typical dishes in a guide and can be disseminated to society.